DAMPAK KENAIKAN TARIF GO-RIDE GOJEK TERHADAP PENDAPATAN DRIVER GO-RIDE DI KECAMATAN PADANG SELATAN - Nilam Putri Cahayati; Yurni Suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
he objectives of this study were (1) to analyze the distribution pattern of the go-ride driver base in South Padang District (2) to analyze the reach of go-ride drivers in Padang Selatan District, and (3) to analyze the income of go-ride go-ride drivers before the increase, after the increase, and when the covid-19 epidemic. This type of research is quantitative. The population of this study were motorbike taxi drivers scattered in pdang Selatan sub-district who are members of an active community. With the sampling technique using total sampling technique, with a total of 80 respondents. In this study, researchers found: (1) The distribution pattern of the Go-Ride Driver Base at 07.00-08.00 WIB, 12.00-13.00 WIB, and at 16.00-17.00 WIB is clustered. (2) The reach of go-ride drivers at 07.00-08.00 WIB, 12.00-13.00 WIB, and 16.00-17.00 WIB in the period before the increase, after the increase, and when the Covid-19 pandemic has different periods, the farthest distance is 20.5 km and the closest distance 0.1 km based on point pick up to destination point. (3) from before the tariff increase, after the tariff increase, and when the Covid-19 pandemic the driver's income decreased, this can be seen from the very high income of 42 people with a percentage of 52.50% experiencing a decrease when after the tariff increase it became 11 people with a percentage 13.75%, and when the Covid-19 pandemic the go-ride drivers of South Padang District did not generate very high income.